Modelling of the coating process on surgical instrumentation with hard chromiun - Jairo Ruiz; Carlos Mario Parra; Carlos Mario Bustamante; Elkin Vélez; Luis Alfonso Rivera (Revista Facultad de Ingeniería Universidad de Antioquia, 2003)
This paper presents a statistical model useful in discribing the behavior of stainless steel surgical needle holders, with a hard cromium coating, in relation to time of exposure, flow density and tempeture variables. It is adjusted by a second order rotational compound experimental design. The proposed model accounts for 75% of the total of the observed responses and due to the complexity of the process involved, it is considered as very satisfactory.